Role of NOS and Inflammatory Markers in the Early Restenosis After the Application of Femoral Arterial Stent: NOS and Inflammatory Markers in the Early Restenosis - Liu, Xuchao; Wei, Chengqi; Ye, Jianjian; Ye, Jiacheng (Cellular and Molecular Biology, 2022)
The objective of this research was to investigate the role of inflammatory markers, including the interleukin-6 (IL-6), matrix metalloprotease 9 (MMP-9), tumor necrotic factor α (TNF-α), endothelin-1 (ET-1) and nitric oxide synthase (NOS) in the early restenosis after the application of femoral arterial stent. According to this, serum samples were collected from the patients who accepted the implantation of arterial stents due to the atherosclerotic occlusive disease in the lower extremities at the following timepoints: 24 h before implantation, 24 h, 1 month, 3 months and 6 months after implantation. With the samples, we detected the levels of IL-6, TNF-α and MMP-9 by using the enzyme-linked immunosorbent assay (ELISA) in serum, levels of ET-1 in plasma by using the non-balanced method of radioimmunity assay and the activity of NOS by using the chemical analysis. Results showed that during the 6-month follow-up, 15 patients (15.31%) reported restenosis; at postoperative 24 h, the level of IL-6 in the restenosis group was much lower than that of the non-restenosis group (P < 0.05), while the level of MMP-9 was higher than that of the non-restenosis group (P < 0.01); besides, at postoperative 24 h, 1, 3, and 6 months after the operation, the average level of ET-1 in the restenosis group was higher than that in the non-restenosis group (P < 0.05 or 0.01). In the restenosis group, the level of NOS in the serum of patients after the implantation of the stent decreased evidently, which was rescued by the treatment of atorvastatin in a dose-dependent manner (P < 0.05). In conclusion, at postoperative 24 h, the levels of IL-6 and MMP-9 increased, while the level of NOS decreased, and the level of ET-1 in the plasma of restenosis patients keeps higher than the baseline.